Work Process of Bring Your Own Device to Support Green Computing - Mohd Yusri Jusoh; Haryani Haron; Jasber Kaur (Institute of Advanced Engineering and Science, 2018)
Bring Your Own Device (BYOD) is a new approach to optimize the use of Information Technology (IT) devices to carry out their work task. The study of BYOD is focused on work activities that perform by IT worker using IT device in public sector. Work activities can provide important insights into IT device portfolio development, end-user segmentation process and the role of IT workers in public sector. The propose of this study is to explore work process of bringing your own devices to support green computing. A conceptual framework of BYOD work process in public sector through integration of IT devices and end-user segmentation to support green computing was developed based on systematic literature review to highlight the implementation of BYOD. This framework considers that work activities based on IT worker, IT device portfolio and end-user segmentation are the main key for public sector to support green computing. This framework is an initial research for researchers and practitioners to further examine BYOD practices in public sector. In addition, to highlight an important gap, this paper explains how different work activities using different IT device influence the IT worker to select the suitable IT device for BYOD that support green computing.